Strategic Human Resource Management and Performance of Selected Deposit Money Banks in Abuja, Nigeria - Marcus Garvey ORJI; Babatunde Kizito OLANIYI; Thomas Oyetunde OLADELE; Abe MHIRNA (Britain International for Academic Research (BIAR) Publisher, 2022)
The objective of this study was to assess the impact of strategic human resource management (extensive training, empowerment, performance appraisal and performance based pay) on organizational performance (service quality) of selected deposit money banks in Abuja. The study was a survey research sampling the opinion of 77 staff of Zenith, Polaris, First bank and First city monument bank, Bwari branch. Their opinion was collected using a structured questionnaire. The data obtained was analysed using descriptive and inferential statistics. The hypotheses were tested by means of correlation and multiple regressions. The study found significant relationship between extensive training, empowerment and performance based pay and service quality. There is also significant relationship between performance appraisal and service quality. The study concluded that Strategic Human Resource Management (SHRM) is important for improved service quality in Nigerian deposit money banks and therefore recommended among others the necessity for every staff of banks to be properly equipped with the skills, technical know-how required to carry out their task effectively; Training programs should target specific need areas of the employees and this should be organized timely given the rate of market and technology changes; Performance appraisal should be centred on pointing out the strength of the employees whilst addressing ways to improve them in areas where they are weak. Also Banks’ human resource management should formulate and implement an active reward policy linked to the overall banks strategy. The reward policy should ensure that employees’ rewards are matched with the employees’ efforts.